Wardlaw's perspectives in nutrition (Bantam Books, 2016)
Instructors will have the ability to assign auto-graded coursework and tutorials that are assessed against Learning Outcomes. The textbook content also serves as the basis for an adaptive, diagnostic self-learning tool for students that will help them acquire mastery and improved grades